PENINGKATAN KEMAMPUAN GURU DALAM PEMBELAJARAN MELALUI PELATIHAN BERBASIS LESSON STUDY - SUPENDI SUPENDI (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2022)
Lesson study implementation has not yet been tried in SMP Negeri 2 Lebaksiu, Tegal Regency. For this reason, in the context of implementing the process standards contained in the National Education Standards, learning in grades seven, eight, and nine is more appropriate if managed in integrated learning through a Lesson study approach. At SMP Negeri 2 Lebaksiu, Tegal Regency, the author tries to train teachers to make lesson plans as well as practice implementing the Lesson study-based learning process. The purpose of this PTS writing is to find out how to increase the ability of teachers in PBM through Lesson study-based training and to find out how much improvement the teacher's abilities in PBM are through Lesson study-based training actions at SMP Negeri 2 Lebaksiu, Tegal Regency. The research was carried out at SMP Negeri 2 Lebaksiu, Tegal Regency, semester I for the 2020/2021 academic year. The research subjects in this study were teachers from class VII to class IX at SMP Negeri 2 Lebaksiu, Tegal Regency. Data collection techniques and tools were carried out through test and non-test instruments. This research consisted of two cycles with each cycle consisting of: planning, action, observation and reflection. The results showed that the results of the pre-cycle average score of 44.34 participants, the first cycle the average value of the participants was 42.60, and the average score in the second cycle was 82.17. While the increase in value based on the percentage from the pre-cycle to the first cycle minus 2.00%, from the first cycle to the second cycle 31.71%, and from the pre-cycle to the second cycle 29.90%. The results of product tests and PBM assessments from cycle I to cycle II showed an increase, namely 17.10% for the increase in RPP products and 23.49% for PBM assessments. Thus it can be concluded that through Lesson study-based training can assist teachers in preparing lesson plans that have a major impact on PBM. ABSTRAKPelaksanaan Lesson study ternyata belum dicobakan di SMP Negeri 2 Lebaksiu Kabupaten Tegal. Untuk itu dalam rangka implementasi standar proses yang termuat dalam Standar Nasional Pendidikan, maka pembelajaran pada kelas tujuh, delapan, dan sembilan lebih sesuai jika dikelola dalam pembelajaran terpadu melalui pendekatan pembelajaran Lesson study. Di SMP Negeri 2 Lebaksiu Kabupaten Tegal penulis mencoba melatih guru membuat RPP sekaligus berlatih melaksanakan proses pembelajaran berbasis Lesson study. Tujuan dari penulisan PTS ini adalah ingin mengetahui peningkatkan kemampuan guru dalam PBM melalui pelatihan berbasis Lesson study dan ingin mengetahui seberapa peningkatan kemampuan guru dalam PBM melalui tindakan pelatihan berbasis Lesson study di SMP Negeri 2 Lebaksiu Kabupaten Tegal. Penelitian dilaksanakan di SMP Negeri 2 Lebaksiu Kabupaten Tegal semester I tahun pelajaran 2020/2021. Subjek penelitian dalam penelitian ini adalah guru-guru kelas VII sampai dengan kelas IX di SMP Negeri 2 Lebaksiu Kabupaten Tegal. Teknik dan alat pengumpulan data dilakukan melalui instrumen tes dan non tes. Penelitian ini terdiri dari dua siklus dengan masing-masing siklus terdiri dari: perencanaan, tindakan, pengamatan dan refleksi. Hasil penelitian menunjukkan bahwa hasil prasiklus nilai rata-rata peserta 44,34, siklus I nilai rata-rata peserta 42,60, dan Hasil nilai rata-rata pada siklus II 82,17. Sedangkan peningkatan nilai berdasarkan prosentase dari prasiklus ke siklus I minus 2,00%, dari sikus I ke siklus II 31,71 %, dan dari prasiklus ke siklus II 29,90%. Hasil tes produk maupun penilaian PBM dari sikus I ke siklus II ada peningkatan, yaitu 17,10% untuk peningkatan produk RPP dan 23,49% untuk penilaian PBM. Dengan demikian dapat disimpulkan bahwa melalui pelatihan berbasis Lesson study dapat membantu guru dalam menyusun RPP yang berpengaruh besar terhadap PBM.